La radioactivite artificielle des sediments transportes par le Danube dans la Mer Noire - Șerbănescu, O.; Iorgulescu, A. (Cercetări Marine - Recherches Marines, 2026)
The surface sediments collected in 1969 and 1970 from the Danube (upstream its mouths) and from the sea, at a depth of 8 m showed a significant, relatively Intense betta and gamma activity. The spectrometric analysis showed the presence of the following radionuclides: 105Ru + 105Rh, 54Mn, 65Zn, 60Co, 144Ce + 144Pr.